Increasing linc00261 expression may predict well cancer prognosis, based on the meta-analysis - Xinyue He; Shixu Fang; Chen Wu; Jintong Na; Liping Zhong; Xiyu Liu (Discover Oncology)
Abstract Background linc00261 was reported to be deregulated in many tumor groups and was significantly associated with cancer prognosis. This investigation seeks to conduct a meta-analysis to explore the link between linc00261 levels and cancer outcomes. Methods Electronic databases underwent comprehensive searching, and appropriate publications were filtered per the predetermined selection criteria. For each included literature, we implemented a quality assessment (NOS score) and obtained relevant data in detail. The link between linc00261 level and cancer outcomes was investigated through pooled HR and OR analysis with 95%CI. Sensitivity analysis was utilized to examine the stability and dependability of the consolidated findings. In the meantime, Begg’s test was carried out to evaluate whether there exists significant publication bias or other bias in the original literature. Results The linc00261 level exhibited reduction in the majority of tumor tissues, where enhanced linc00261 levels demonstrated substantial correlation with favorable cancer outcomes, encompassing overall survival (OS) (hazard ratio (HR): 0.497, 95% CI: 0.408–0.586), disease-free survival (DFS) (HR: 0.38, 95% CI: 0.25–0.59) and progression-free survival (PFS) (HR: 0.31, 95% CI: 0.18–0.53). Moreover, increased linc00261 levels indicated earlier TNM stages (odds ratio (OR): 0.542, 95%CI: 0.442–0.663), reduced susceptibility to distant lymph node metastasis (LNM) (OR: 0.674, 95%CI: 0.550–0.826), distant metastasis (DM) (OR: 0.579, 95%CI: 0.420–0.798), reduced tumor size (OR: 0.705, 95%CI: 0.564–0.880) and improved histological grade (OR: 0.906, 95%CI: 0.694–1.183). Sensitivity analysis outcomes suggest that individual studies demonstrate minimal influence on the comprehensive findings. The Begg’s test outcomes suggest that the original study had no significant publication or other biases. Conclusions The expression of linc00261 is decreased in many tumor tissues, high linc00261 expression indicates a satisfied prognosis of cancer. linc00261 could function as a candidate therapeutic target and an encouraging prognostic indicator for tumors.